Case Report: Combination Therapy With PD-1 Blockade for Acute Myeloid Leukemia After Allogeneic Hematopoietic Stem Cell Transplantation Resulted in Fatal GVHD - Yao, Sun; Jianlin, Chen; Zhuoqing, Qiao; Yuhang, Li; Jiangwei, Hu; Guoliang, Hu; Hongmei, Ning; Bin, Zhang; Liangding, Hu (Frontiers in Immunology, 2021)
Background: Azacitidine is commonly used in the treatment of relapsed acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) after allogeneic hematopoietic stem cell transplantation (allo-HSCT), but the effectiveness of this monotherapy is still very low. A possible mechanism of resistance to hypomethylating agents (HMAs) is the upregulation of the expression of inhibitory checkpoint receptors and their ligands, making the combination of HMAs and immune checkpoint blockade therapy a rational approach. Although the safety of anti-programmed cell death protein (PD)-1 antibodies for patients with post-allo-HSCT remains a complicated issue, the preliminary clinical result of combining azacitidine with anti-PD-1 antibodies is encouraging; however, the safety and efficacy of this approach need further investigation. Case Presentation: We reported a case of treated secondary (ts)-AML in a patient who received tislelizumab (an anti-PD-1 antibody) in combination with azacitidine. The patient relapsed after allo-HSCT and was previously exposed to HMAs-based therapy. The patient received tislelizumab for compassionate use. After the combination treatment, the patient achieved complete remission with incomplete hematologic recovery, negative minimal residual disease (MRD) by flow cytometry (FCM), and negative Wilms' tumor protein 1 (WT1). However, the patient successively developed serious immune-related adverse events (irAEs) and graft vs. host disease (GVHD) and eventually died from complications of GVHD. Conclusion: To our knowledge, this is the first case to report the combined use of tislelizumab and azacitidine to treat relapsed AML posttransplantation. This report highlights the safety concerns of using an anti-PD-1 antibody in combination with azacitidine after allo-HSCT, especially the risk of GVHD, and provides a basis for future studies.